Green-smart service quality and halal tourism attributes on revisit intention and quality of life: A case study from Indonesia - Alfarizi, Muhammad; Ngatindriatun, Ngatindriatun; Arifian, Rafialdo; Widiharjanti, Isti (International Journal of Halal Industry, 2025)
Purpose – This study aimed to analyze the factors that affect tourist satisfaction and loyalty in the context of halal tourism in Indonesia. This study also explores the role of halal destination attributes and the use of technology in improving the experience of Muslim tourists. Methodology – This study uses a quantitative approach with partial least squares structural equation Modeling (PLS-SEM). Data were collected through a survey of 200 respondents with halal tourism experiences at various destinations in Indonesia. The analysis was conducted to evaluate the validity and reliability of the construct and to test the causal relationships between variables. Findings – The results show that the image of halal destinations, sharia-based tourism facilities, and the application of smart technology have a significant impact on tourist satisfaction. Additionally, tourist satisfaction affects the intention to return visits, which is an indicator of tourist loyalty. Factors such as availability of halal food, worship facilities, and strong destination imagery contribute to increasing the attractiveness of halal tourist destinations. Implications – These findings provide insights for halal tourism industry stakeholders to develop more effective marketing and service strategies. Strengthening halal infrastructure and utilizing digital technology can increase Indonesia's competitiveness as a major destination for halal tourism globally. Originality – This study contributes by integrating aspects of digital technology in the study of halal tourism, an approach that has rarely been explored in previous research. This study also highlights the role of destination imagery in shaping Muslim tourist loyalty.